2020
DOI: 10.1017/s1047951119003196
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic examination of mitral valve abnormalities in the paediatric population: current practices

Abstract: We reviewed the recent literature for echocardiographic assessment of mitral valve abnormalities in children. A literature search was performed within the National Library of Medicine using the keywords “mitral regurgitation and/or stenosis, children.” The search was refined by adding the keywords “echocardiographic definition, classification, and evaluation.” Thirty-one studies were finally included. Significant advances in echocardiographic imaging of mitral valve defects, mainly due to the implementation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Building on existing data from adults with heart failure, Neubauer et al identified six common psychological, emotional, and cognitive transitions in families after a life-limiting pediatric cardiac diagnosis [ 12 ]. Clearly, parents are at risk for experiencing intense and complex psychosocial stress as early as the prenatal period, and remain vulnerable through surgery and beyond [ 12 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Building on existing data from adults with heart failure, Neubauer et al identified six common psychological, emotional, and cognitive transitions in families after a life-limiting pediatric cardiac diagnosis [ 12 ]. Clearly, parents are at risk for experiencing intense and complex psychosocial stress as early as the prenatal period, and remain vulnerable through surgery and beyond [ 12 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Building on existing data from adults with heart failure, Neubauer et al identified six common psychological, emotional, and cognitive transitions in families after a life-limiting pediatric cardiac diagnosis [ 12 ]. Clearly, parents are at risk for experiencing intense and complex psychosocial stress as early as the prenatal period, and remain vulnerable through surgery and beyond [ 12 , 16 , 17 ]. Knowledge of these transitions can allow pediatric PC providers to address a range of issues and adequately support cardiac patients and families during these challenging times, as described in Table 1 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations